2020
DOI: 10.1039/d0sm00176g
|View full text |Cite
|
Sign up to set email alerts
|

Collective forces in scalar active matter

Abstract: Large-scale collective behavior in suspensions of many particles can be understood from the balance of statistical forces emerging beyond the direct microscopic particle interactions. Here we review some aspects of the collective forces that can arise in suspensions of self-propelled active Brownian particles: wall forces under confinement, interfacial forces, and forces on immersed bodies mediated by the suspension. Even for non-aligning active particles, these forces are intimately related to a non-uniform p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 146 publications
(170 reference statements)
1
47
0
Order By: Relevance
“…Key applications of this important and abundant transport mechanism range from micro-fluidics to wastewater treatment [10][11][12][13][14][15][16]. Recently, it has attracted additional interest as an important underlying mechanism for chemo-taxis [17][18][19], non-equilibrium self-assembly [20][21][22][23] and artificial micro-swimming [24][25][26][27][28][29][30][31][32], where a e-mail: namoelle@uni-mainz.de (corresponding author) the gradients are self-generated locally and thus allow for self-organized, persistent directed motion [33]. If such swimmers propagate into a quiescent, pristine environment, they typically show a stationary directed propulsion superimposed by some rotational diffusion [34].…”
Section: Introductionmentioning
confidence: 99%
“…Key applications of this important and abundant transport mechanism range from micro-fluidics to wastewater treatment [10][11][12][13][14][15][16]. Recently, it has attracted additional interest as an important underlying mechanism for chemo-taxis [17][18][19], non-equilibrium self-assembly [20][21][22][23] and artificial micro-swimming [24][25][26][27][28][29][30][31][32], where a e-mail: namoelle@uni-mainz.de (corresponding author) the gradients are self-generated locally and thus allow for self-organized, persistent directed motion [33]. If such swimmers propagate into a quiescent, pristine environment, they typically show a stationary directed propulsion superimposed by some rotational diffusion [34].…”
Section: Introductionmentioning
confidence: 99%
“…The Smoluchowski equation has been employed, to within certain approximations, to analyse the stability of MIPS in 2D [25][26][27][28][29] . Here, a linear decrease of the average velocity v ∼ v 0 ( 1 − ζ ρ) of swimmers with increasing concentration ρ is found (with v 0 the free-swimming velocity), which is in accordance with semiemperical approaches 30,[32][33][34] , and with simulations in 2D 35 .…”
Section: Introductionmentioning
confidence: 99%
“…observed that reflecting boundary conditions do not recover the behaviour observed in experiments. Other groups did not try to prescribe any specific law for swimmers at a boundary and focused on statistics such as the invariant density of swimmers (Ezhilan et al 2012;Yariv & Schnitzer 2014;Yan & Brady 2015;Malgaretti & Stark 2017) and swim pressure (Caprini & Marconi 2018;Chen et al 2018;Yan & Brady 2015;Speck 2020).…”
Section: Previous Workmentioning
confidence: 99%